Abiding Faith : Christianity Beyond Certainty, Anxiety, and Violence. - Cowdell, Scott (James Clarke & Co, 2010)
Australian theologian Scott Cowdell explores how having faith has changed under the influence of modernity and post-modernity in the West. He returns faith from pious sentimentality and arid philosophy of religion to the realm of participating knowing, paradigmatic imagination, and personal transformation where it belongs as a form of life, shaped by encounter with Jesus Christ and worked out through the Eucharistic community. This is shown to have been the typical understanding of faith from Saint Paul to the Fathers to the medieval monastic theologians. Since the rise of nominalism, however,